Comparative Effects of Rocabado Exercises and Myofascial Release on Pain in Patients with Temporomandibular Joint Dysfunction - Salahuddin, Saman; Afzal, Iqra; Ayub, Gulraiz; Zahir, Sana; Babar, Syed Saqlain; Tariq, Ruhma; Mehmood, Mariam (Indus Journal of Bioscience Research, 2025)
Background: The study was conducted to compare the effects of Rocabado exercises and myofascial release technique (MFR) in minimizing pain in patients with TMJ (Temporomandibular Joint) dysfunction. Method: A randomized clinical trial was conducted on a sample of 30 patients recruited by purposive sampling technique from physiotherapy and dental OPDs of Madinah Teaching Hospital and Allied Hospital Faisalabad were divided into two groups by lottery method. Ultrasound therapy and simple jaw exercises were given as baseline treatment to both groups. Group A received Rocabado 6X6 exercises while Group B received MFR at temporomandibular joint area thrice a week for 4 weeks. Before and after treatment readings were taken from each participant using Numeric Pain Rating Scale (NPRS). Results were analyzed through SPSS version 20. Results: The study findings suggested that outcome measure had not shown statistically remarkable difference upon comparison between two groups. The p value for NPRS turned out to be greater than 0.05 which suggested non-significant differentiation between two groups. Conclusion: The outcome of this study had drawn to conclude that both Rocabado Exercises and Myofascial Release Technique were statistically significant in decreasing pain in subjects with Temporomandibular Joint Dysfunction Syndrome (TMJD).